Mechanisms involved in the uptake of nanofertilizers in the soil-plant system: A review - Dhara, H; Rathod, S; Timothy , L; Tirtharaj, P; Kenny , Z; Tasvina, R B; Helim, R (Plant Science Today, 2025)
To meet the demands of a projected population of nine billion people by 2050, a minimum 50 % increase in food production requires advanced technological interventions, considering the increasing deterioration of water and land resources. Nanotechnology initiatives have been launched to improve the agricultural sector, taking into account the exceptional properties of nanoparticles. The increasing application of nanotechnology in agriculture relies on several factors, including established effects, potential toxicity, monitored environmental fate and overdose thresholds. Plants are integral to ecosystems and nanoparticles can interact with their environment, including plant systems. Nanoparticles can engage with plants, affecting their absorption and accumulation in plant biomass, hence modifying their environmental fate and movement. Nanoparticles can penetrate living plant tissues. This has significant implications for their aggregation behaviour in ecosystems and their potential role as intelligent delivery systems within plants. Determining the ability of plants to absorb and transport intact nanoparticles is essential for various plant tissues. Precise dosage and effectiveness of nanoparticles on plant target surfaces represent a significant challenge. Minimising the dispersion of chemical products from bulk materials, such as mineral fertilisers, has emerged as a beneficial characteristic that enhances the possible application. To govern the role of nanoparticles within and outside of plants and their environmental implications, rigorous research under controlled settings is essential. Formulating an application strategy requires a thorough evaluation of nanoparticle dosage, exposure duration, translocation and accumulation patterns and mechanisms of action within plants.